Emergent treatment using balloon-assisted ERCP versus EUS-guided drainage for acute cholangitis in patients with surgically altered anatomy - Takahiro Shishimoto; Masahiro Itonaga; Reiko Ashida; Yasunobu Yamashita; Yuki Kawaji; Takashi Tamura; Hiromu Morishita; Akiya Nakahata; Yuto Sugihara; Tomokazu Ishihara; Masayuki Kitano (International Journal of Gastrointestinal Intervention)
Background : No studies have compared balloon-assisted endoscope-guided endoscopic retrograde cholangiopancreatography (BAE-ERCP) and endoscopic ultrasonography-guided biliary drainage (EUS-BD) for emergent treatment of acute cholangitis (AC) in patients with upper gastrointestinal surgically altered anatomy (SAA). Methods : This study retrospectively evaluated consecutive patients who underwent emergent BAE-ERCP or EUS-BD for AC with SAA between January 2020 and March 2024. Technical success, clinical success, procedure time, and adverse events (AEs) were compared between the two groups. Results : This study included 23 patients in the BAE-ERCP group and 14 patients in the EUS-BD group. Technical success and clinical success rates did not significantly differ between the two groups (88% vs. 100%, P=0.51 and 95% vs. 93%, P=0.66). Similarly, the rate of AEs was comparable between the two groups (4% vs. 14%, P=0.54). The median procedure time was significantly shorter in the EUS-BD group than in the BAE-ERCP group (32.5 [interquartile range; IQR, 28.8-52.5] minutes vs. 70.0 [IQR, 60.0-90.0] minutes, P<0.01). In cases with grade 2 or 3 cholangitis, the rates of technical success, clinical success, and AEs did not significantly differ between the two groups. However, the median procedure time was significantly shorter in the EUS-BD group than in the BAE-ERCP group (32.5 [IQR, 28.8-52.5] minutes vs. 70 [IQR, 56.3-90.0] minutes, P<0.01). Conclusion : While both BAE-ERCP and EUS-BD can be performed safely and effectively in patients with AC and SAA, the procedure time is significantly shorter with EUS-BD than with BAE-ERCP.